Establishment of Lipid Profile Reference Intervals in a Sample Population of Halabja City, Kurdistan Region of Iraq - Baqi, Hardi Rafat; Abdullah, Tareq Hamaamin; Ghafor, Dashty Aziz; Karim, Salar Husein (Iraqi Journal of Science, 2021)
Every laboratory needs to establish its own community-based reference intervals for the achievement of the optimal and true diagnosis in the clinical practice. However, such vital experimentations are not been conducted sufficiently in Halabja city and Kurdistan region of Iraq as a whole. This study is an attempt to introduce for the first time a set of reference intervals of lipid profile variables that are based on the healthy and asymptomatic adult population of Halabja using international standards. The methodology recruited for this purpose is based on the IFCC, CLSI, and WHO’s standards, in which the study population was subjected to strict exclusion criteria for the sake of higher accuracy in the results. The reference intervals are computed as the 95th percentile of the lipid profile variable values. The results are broken down based on the gender and age groups. All of the estimated intervals fall perfectly in the internationally known reference intervals. Even so, the outcome values are similar and sometimes higher than the currently used intervals by the laboratories and physicians for the diagnosis purposes. The out-turns from the study encourage us to demand the healthcare providers to reconsider the currently approved reference intervals for the lipid profile test (TC, TG, HDL-C, LDL-C, and VLDL-C) in the clinical practice and consider the results of this study for further diagnostic purposes.